The willingness to be vaccinated against SARS-CoV-2 in the Italian population. (20th October 2021) - Contoli, B; Minardi, V; Possenti, V; Lana, S; Luzi, P; Masocco, M
Abstract: Background: Italy was one of the earliest countries to experience a severe Covid-19 epidemic and vaccination is essential to controll it. The willingness to be vaccinated against Covid-19 was investigated by the Italian ongoing ;surveillance systems PASSI (18-69yy) and PASSI d'Argento (65+) with a Covid module added in August 2020. Methods: To measure the prevalence of hesitancy and refusal to receive the COVID-19 vaccine, we used a sample collected between August and December 2020, before starting the Covid-19 vaccination campaign. Sample was appropriately weighted to take into account the regional number and the composition by gender and age. Using a multinomial regression model, a specfic analysis on elderly data were provided to examine the association between demographic and medical characteristics and Covid-19 attitudes. Results: Among adults, 67% answered to be likely accepting the vaccine (one half not hesitating at all and the other half very likely in any way); younger individuals, aged 18-34, are highly incline (76%). On older sample, 55% would accept vaccination and 16% would likely refuse; the remaining 29% were categorized as hesitant. Compared with the acceptance group, the hesitancy group identified several risk factors in common with the refusal group, including not having gotten a flu vaccine during the previous flu season (hesitancy: RRR=2.0; 95% CI 1.4-2.9, refusal: RRR=12.1; 95%CI 7.6-19.37) and lower risk of having had a death from Covid-19 among family or friends (hesitancy: RRR=4.8; 95%CI 2.0-11.4, refusal: RRR=15.4; 95%CI 3.7-64.5). Hesitancy group has also lesser awareness and experience with the disease, a lower perception of being personally at risk and lower trust in the ability of health units to manage the pandemic situation. Conclusions: Results show the importance of establishing and maintaining ongoing contact among the preventive services, primary care providers and the population since trust is difficult to establish during an emergency. Key messages: On of the most important finding for public health prevention efforts was the importance of influenza vaccine in predicting COVID. Having an agile system that can monitor changing attitudes will be important to altering the messaging and identifying changes in the characteristics of those hesitant or unwilling to be vaccinated.